Use of carqueja (Baccharis trimera(Less.) DC. Asteraceae) as a total substitute for hops in the production of lager beer - Schuina, Guilherme Lorencini [UNESP]; Quelhas, Joao Olavo Figueiredo [UNESP]; Carvalho, Giovani Brandao Mafra de; Del Bianchi, Vanildo Luiz [UNESP] (Wiley-Blackwell, 2020)
This work aimed to evaluate carqueja as a substitute for hops in the production of craft lager beers. Six beers were produced, one using hops, and five using different carqueja concentrations (1 to 5 g/L), and evaluated alongside a commercial beer. Physicochemical (apparent extract, original gravity, alcohol content, pH, color, turbidity, apparent attenuation, and bitterness) and sensory (acceptance, bitterness intensity, ideal bitterness intensity, and purchase intention) analyses were performed, allowing us to conclude that the substitution of hops with carqueja had no negative effects on beer's physicochemical characteristics. Regarding sensory characteristics, sensory acceptance was similar for all the experimental beers made, and for the commercial beer. Our results show that carqueja can be a viable alternative for hops substitution in craft low-bitter beer production. Practical applications This work describes a new approach to produce beer without using hops. Carqueja is a vegetable well found and produced in Brazil, while hops have negative aspects in the cultivation in this country. The study demonstrated that carqueja beer has sensory acceptance similar to the hop beer, and the carqueja bitterness was, by the evaluators, close to the ideal bitterness in beer.